Assessment of the effectiveness of relative accounting methods for micromammals under the conditions of anthropogenic impact of northern Kazakhstan - Zakanova, A.N.; Yerzhanov, N.T.; Litvinov, Yu.A.; Sergazinova, Z.M. (Fundamental and Experimental Biology, 2022)
Accounting methods for the number of organisms are divided into absolute and relative. The article provides a comparative assessment of the relative methods for small mammals catching. There is theoretical and practical information on the method of accounting using crushers and the method of trapping grooves in the article. The article presents the methodological aspects of using Gero traps and trapping cylinders and a comparative assessment of the results of using two methods of accounting in a sharply continental climate and steppe habitat of micromammals. Recommendations are given on the use of relative methods of accounting for terrestrial chordates. The study continued throughout 2020, 2021 on the territory of the Pavlodar region in areas with an increased anthropogenic impact and the territory located 100 km from the nearest cities and factories. When using the trap method, there is a wide variety of species caught and there are more of them compared to the crusher method. The temporal characteristics of the use of accounting methods are considered: the peak of indicators is observed in the spring-summer period, namely from May to August in both methods of accounting for the number of mammals. Biotopes located far from large settlements have higher species diversity in comparison with the habitat near industrial plants. On the territory of the Pavlodarregion, the advantage of using the method of trapping grooves was established in comparison with the method of crushers when taking into account small mammals.